2008
DOI: 10.1053/j.semperi.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Adult Sequelae of Intrauterine Growth Restriction

Abstract: Fetal intrauterine growth restriction has been associated with adult disease in both human epidemiologic studies and in animal models. In some cases, intrauterine deprivation programs the fetus to develop increased appetite and obesity, hypertension and diabetes as an adult. Although the mechanisms responsible for fetal programming remain poorly understood, both anatomic and functional (cell signaling) changes have been described in affected individuals. In some animal models, aspects of fetal programming can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 86 publications
(9 reference statements)
2
112
0
5
Order By: Relevance
“…We present evidence for the first time that suppressed expression of LXRa may mediate the enhanced transcription of the gluconeogenic genes G6pase and 11b-Hsd1 due to its decreased binding on these promoters, ultimately removing its ability to suppress hepatic gluconeogenesis (Stulnig et al 2002a, Cao et al 2003, Laffitte et al 2003, Mitro et al 2007). Given placental insufficiency in humans can produce protein deficiency in the fetus (Crosby 1991), this LP model shares features in common with PI-IUGR (Ross & Beall 2008). Previous studies done in our laboratory with the same cohort of animals have already demonstrated that LP offspring exhibit a 15% lower fetal to placental weight ratio and a 40% decreased fetal liver to body weight ratio at embryonic day 19 (Sohi et al 2011).…”
Section: Discussionmentioning
confidence: 73%
“…We present evidence for the first time that suppressed expression of LXRa may mediate the enhanced transcription of the gluconeogenic genes G6pase and 11b-Hsd1 due to its decreased binding on these promoters, ultimately removing its ability to suppress hepatic gluconeogenesis (Stulnig et al 2002a, Cao et al 2003, Laffitte et al 2003, Mitro et al 2007). Given placental insufficiency in humans can produce protein deficiency in the fetus (Crosby 1991), this LP model shares features in common with PI-IUGR (Ross & Beall 2008). Previous studies done in our laboratory with the same cohort of animals have already demonstrated that LP offspring exhibit a 15% lower fetal to placental weight ratio and a 40% decreased fetal liver to body weight ratio at embryonic day 19 (Sohi et al 2011).…”
Section: Discussionmentioning
confidence: 73%
“…lead to increased cardiovascular risk later in life (33,34) . The fact that high as compared with low NND adherence also implied an estimated 7 % higher adjusted odds of the infant being born LGA indicates that factors associated with better diet quality may improve fetal substrate availability and enhance fetal growth in general.…”
Section: Discussionmentioning
confidence: 99%
“…22 The introduction of formula in the neonatal period for infants with intrauterine growth restriction, as a total or partial replacement for breastfeeding, provides a sodium content three times greater than those receiving exclusive breastfeeding. 23,24 In addition, it may also be observed that lowbirth-weight infants present vascular endothelial dysfunction, and this situation can be aggravated by a short duration of breastfeeding, possibly increasing the biological risks associated with low birth weight.…”
mentioning
confidence: 99%